Histological effect of Curcuma longa and Zingiber officinale on the liver damage after treatment with hydrogen peroxide in Rats (Rattus norvegicus) - Al-Muswie, Rana Talib; Al-rekab, Eman A.; Al-Asadi , Noor Ali Badir (University of Thi-Qar Journal, 2019)
This research is aimed at investigating the hepatotoxic effect of hydrogen peroxide and effects of Curcuma longa and zingiber officinale on this hepatotoxicity. In present study we administration hydrogen peroxide to animals rat for induced high cholesterol in blood and caused liver damage . These were carried out via estimation of liver function tests and histochange in the liver. Fourteen adult Westar rats Rattus norvegicus were used for the experimental investigations. They were grouped into four groups:. Animals in group one served as the control group. Group two consists of rats administered with hydrogen peroxide (1% body weight) .Group three consists of rats administered with hydrogen peroxide and Curcuma longa (200 mg/ kg body weight).Group four administered with hydrogen peroxide and zingiber officinale(200 mg/ kg body weight). All animals administration orally, the experimental period lasted for 30 days. The rats were sacrificed on the thirteen day. The blood samples collected by cardiac puncture and placed in appropriately labeled bottles for the various assays. And section of liver isolated. There was a decrease in the aspartate aminotransaminase level, alanine aminotransferase level are significantly lower (P<0.05) in the rats of the control group than both the rats treated with hydrogen peroxide only and the ones treated peroxide with Curcuma longa and peroxide with zingiber officinale These were lower in the rats treated with Curcuma longa and zingiber officinale than the rats treated with hydrogen peroxide alone. These reduction is however not statistically significant and it presents that these could be dosage related. The histological change in the section of liver showed as clusters of inflammatory cells surrounding portal area or within the parenchyma was seen. Vacuation within hepatocytes and congestion in centeral vien were observed and was generally necrosis hepatocytes compare compared with animals treatment in extracts a decreasing in degenerative changes was noticed in proxide + curcuma extract, there was a moderate decreasing of hepatocellular damage and portal tract fibrosis, inflammatory infiltration compared to peroxide group .But in the fourth group zingiber +hydrogen peroxide no hepatocellular damage,. It was noticed that this group has the same histological appearance as the control group. These results indicate that hydrogen peroxide is induce to increase the cholestrole and caused hepatotoxic but that Curcuma longa and zingiber officinale may be a protective effect on this hepatotoxicity.